Measuring the nationalism index of Malaysian nation in less developed states - Sanusi, Nur Azura; Ghazali, Normi Azura; Abdullah, Mohd Lazim; Golam Hassan, Asan Ali; Habibullah, Muzafar Shah; Kusairi, Suhal (2015)
Generally, Malaysia must reached the minimum level outlined by world bodies such as the OECD, World Bank and United Nations to be classified as a developed country.Therefore, states that target to become developed state status also needs to reach the minimum level stipulated by the world bodies for inline recognized as a developed country. The progress to be achieved by Malaysia is not limited to economic and social, but also includes spiritual, psychological and cultural community. Malaysia target was stated in the 9 challenges of Vision 2020, which to create a united Malaysian nation.Therefore, the objective of this study to measure the nationalism index of Malaysian people towards the establishment of 'bangsa Malaysia' as set out in Vision 2020.The study involved 504 respondents from five less developed states in Peninsular Malaysia, namely Kedah, Perlis, Pahang, Terengganu and Kelantan.A structured interview technique using a questionnaire was conducted to qualitatively determine the public perception of the formation of the Malaysian nation.Data was analyzed using fuzzy sets approach.The results showed that the index of nationalism and unity of Perlis residents higher than other states.